The Effect of Different Concentration of Yellow Yam Flour (Dioscorea alata) on The Characteristic of Wet Noodles: Yellow yam tuber for wet noodles - Lavlinesia, Lavlinesia; Kurniadi, Irwan; Ulyarti, Ulyarti (Jurnal Bio-Geo Material Dan Energi, 2022)
Yam (Dioscorea alata) is a species of tubers that have carbohydrates and starch as well as having the fiber as an added value which can be processed into noodles. Fiber is the part of the plant that can not be digested. This study aimed to determine the amount of wild yam flour, fiber content and organoleptic properties in a wet noodle flour substitution with wild yam flour. Parameter observed moisture, resilience, crude fiber, cooking loss, and organoleptic. The method used experimental method completely randomized design with a 5 stage treatment of the addition of wild yam flour as much as 0% (P0), 10% (P1), 20% (P2), 30% (P3) and 40% (P4) with 4 times repetition. The data were analyzed using ANOVA followed DNMRT test with confidence interval of 5%. The analysis showed that the addition of wild yam flour influence on the physical, chemical and organoleptic. The best noodles parameters that have a water content of 59.83%, resilience 25.75%, crude fiber 0.27%, cooking loss 1.72, texture 3.65 (rather chewy), flavor 3.90 (rather like), and the overall acceptance 4.25 (like).